2013
DOI: 10.5966/sctm.2012-0110
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Epicenter Versus Intact Parenchyma as a Transplantation Site for Human Neural Stem Cells for Spinal Cord Injury Therapy

Abstract: Neural stem cell transplantation may have the potential to yield repair and recovery of function in central nervous system injury and disease, including spinal cord injury (SCI). Multiple pathological processes are initiated at the epicenter of a traumatic spinal cord injury; these are generally thought to make the epicenter a particularly hostile microenvironment. Conversely, the injury epicenter is an appealing potential site of therapeutic human central nervous system-derived neural stem cell (hCNS-SCns) tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 47 publications
9
61
0
Order By: Relevance
“…In concordance with our previous transplantation studies using a single donor human cell dose (Piltti et al., 2013a, Piltti et al., 2013b), no significant interaction was found between the number of forepaw or hindpaw withdrawals in the dose groups over time (Figures 7A and 7B, two-way ANOVA p = 0.62 and p = 0.9, respectively). In addition, no significant differences were found between dose groups either pre-transplantation or at 13 WPT (Figures 7A and 7B, Bonferroni post hoc test, p > 0.05), suggesting no relationship between transplant dose and sensory recovery/development of hyperalgesia.
Figure 7Effect of hCNS-SCns Transplantation Dose and Cell Phenotype on Recovery of Sensory and Locomotor Function(A and B) Hargreaves hyperalgesia testing prior to transplantation and at 13 WPT revealed no significant interaction between the number of forepaw or hindpaw withdrawals in the dose groups over time (two-way ANOVA p = 0.62 and p = 0.9, respectively), or significant differences between dose groups either pre-transplantation or 13 WPT (Bonferroni post hoc test, p > 0.05).
…”
Section: Resultssupporting
confidence: 92%
“…In concordance with our previous transplantation studies using a single donor human cell dose (Piltti et al., 2013a, Piltti et al., 2013b), no significant interaction was found between the number of forepaw or hindpaw withdrawals in the dose groups over time (Figures 7A and 7B, two-way ANOVA p = 0.62 and p = 0.9, respectively). In addition, no significant differences were found between dose groups either pre-transplantation or at 13 WPT (Figures 7A and 7B, Bonferroni post hoc test, p > 0.05), suggesting no relationship between transplant dose and sensory recovery/development of hyperalgesia.
Figure 7Effect of hCNS-SCns Transplantation Dose and Cell Phenotype on Recovery of Sensory and Locomotor Function(A and B) Hargreaves hyperalgesia testing prior to transplantation and at 13 WPT revealed no significant interaction between the number of forepaw or hindpaw withdrawals in the dose groups over time (two-way ANOVA p = 0.62 and p = 0.9, respectively), or significant differences between dose groups either pre-transplantation or 13 WPT (Bonferroni post hoc test, p > 0.05).
…”
Section: Resultssupporting
confidence: 92%
“…Cadaveric targeting error with SpinoBot was nearly identical to results presented herein 5. Precise targeting will likely be necessary for intra-spinal delivery of therapeutics where accurate guidance to the ventral horn or within a post-traumatic spinal cord cyst_ENREF_4 may be necessary 29. Potential sources of targeting error in the present study include imperfect guidance of the spinal needle along the trajectory overlay as well as possible cord deformation and distortion with needle insertion.…”
Section: Discussionsupporting
confidence: 70%
“…Intra-spinal delivery of therapeutics would be greatly aided by accurate MRI guidance afforded with this technology. For example, preclinical studies in models of traumatic spinal cord injury have shown that graft survival and differentiation can vary depending on whether cells are transplanted into the epicenter or margins of a contusion injury 29. For many applications, high precision and MRI guidance are both needed to successfully target the ideal location for therapeutic delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Methods and lines used in this study are identical to those described in (Cummings et al 2005; Cummings 2009; Salazar et al 2010; Piltti et al 2013; Piltti et al 2013). Briefly, hCNS-SCns were propagated as neurospheres in X-Vivo 15 medium without phenol red (Lonza, Basel, Switzerland) supplemented with N2, bFGF, EGF, heparin, NAC, and LIF as described previously (Uchida et al 2000; Cummings et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that human central nervous system-derived stem cells propagated as neurospheres (hCNS-SCns) (Uchida et al 2000) exhibit robust engraftment in the injured spinal cord niche after transplantation at acute, sub-acute or chronic stages of injury in immunodeficient rodent models (Cummings et al 2005; Hooshmand et al 2009; Salazar et al 2010; Piltti et al 2013; Piltti et al 2013). Further, when transplanted into an immunodeficient model in which rejection of the xenograft is minimized, human cells were capable of both proliferation and extensive migration (Anderson et al 2011), both of which are normal processes for CNS development (Lui et al ; Hatten 1999; Wilcock et al 2007).…”
Section: Introductionmentioning
confidence: 99%